Extrapulmonary tuberculosis - surgeons' experience at a district hospital: a study of 84 cases - Rahman, M. Shofiur; Akhter, Jafrin; Habib, Ahsan; Akteruuzzaman, (International Surgery Journal, 2024)
Background: Managing extrapulmonary tuberculosis (EPTB) is challenging due to the non-specific signs and symptoms, the low sensitivity of diagnostic tests, and the potential for the disease to mimic other conditions. The aim of the study was to evaluate the clinical characteristics, surgical management, and outcomes of extrapulmonary tuberculosis at a district hospital, based on an analysis of 84 cases. Methods: This prospective study was conducted at the Department of Surgery in collaboration with the Department of Medicine at Magura District Hospital and private clinics of Magura District, Magura, Bangladesh, from January 1, 2013, to December 31, 2018, including 84 patients diagnosed with extrapulmonary tuberculosis. Informed consent was obtained from all participants or their guardians, and data on demographics, clinical presentation, diagnostic tests, and treatment outcomes were analyzed using SPSS version 20. Results: The study showed that 33 (39.29%) patients were aged 21-30 years, with a majority being female 49 (58.33%) and from rural areas 46 (54.76%). All patients had a palpable mass, with the cervical lymph nodes most affected 78 (92.86%). Lymph node tuberculosis was the most common site 55 (65.48%) and chest radiography was negative for tuberculosis in 81 (96.43%) patients. Treatment was medical only for 41 (48.81%) patients and combined medical and surgical for 43 (51.19%) patients. Conclusions: Extrapulmonary tuberculosis, particularly cervical lymph node involvement, remains prevalent in rural, low socio-economic populations, underscoring the importance of comprehensive diagnostic and treatment approaches.